2021
DOI: 10.1186/s13643-021-01585-w
|View full text |Cite
|
Sign up to set email alerts
|

Inflammation scores as prognostic biomarkers in small cell lung cancer: a systematic review and meta-analysis

Abstract: Background Inflammation scores based on general inflammation markers as leucocyte count or C-reactive protein have been evaluated as prognostic markers of inferior survival in several cancers. In small cell lung cancer (SCLC), however, inflammation scores are less studied. In the present study, we set out to perform a systematic review and meta-analysis investigating reported associations between inflammation scores and overall survival (OS) in SCLC. Methods … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 62 publications
1
18
0
Order By: Relevance
“…The nine evaluated inflammation-scores have all previously shown potentials as prognostic biomarkers of OS in lung cancer patients [ 26 29 , 32 , 34 38 ]. NLR is the most widely studied score and has in meta-analyses demonstrated to hold prognostic value in NSCLC [ 39 – 41 ] as well as in SCLC [ 17 , 19 ]. On the other hand, the ACBS has only once been studied in patients with lung cancer as we previously have evaluated the score in 267 patients with NSCLC.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The nine evaluated inflammation-scores have all previously shown potentials as prognostic biomarkers of OS in lung cancer patients [ 26 29 , 32 , 34 38 ]. NLR is the most widely studied score and has in meta-analyses demonstrated to hold prognostic value in NSCLC [ 39 – 41 ] as well as in SCLC [ 17 , 19 ]. On the other hand, the ACBS has only once been studied in patients with lung cancer as we previously have evaluated the score in 267 patients with NSCLC.…”
Section: Discussionmentioning
confidence: 99%
“…In lung cancer, several inflammation-scores have been evaluated. Especially, NLR, PLR and GPS have attracted attention and in meta-analyses demonstrated potentials as prognostic biomarkers independently of stage and histology [ 15 19 ]. However, despite many studies on inflammation-scores in the literature, it remains unknown which inflammation-score serves as the best prognostic score.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lower ALB has been associated with a higher incidence of systemic inflammation and a worse overall survival [9,15]. Additionally, a higher CRP concentration and a greater Neutrophil to Lymphocyte Ratio (NLR) have been related to a worse overall survival in LC [9,15,16]. An adequate protein and energy intake represents the first target of a correct nutritional intervention in cancer patients [15].…”
Section: Introductionmentioning
confidence: 99%
“…11–13 However, conflicting results of monocytes/lymphocytes (MLR), platelets/lymphocytes (PLR), circulating neutrophils/lymphocytes (NLR) and prognosis of lung cancer have been reported. 14–16 Hou et al 17 indicated that fibrinogen (FIB) and D-dimer levels could be used as candidate biomarkers for the prognosis of NSCLC. It can be inferred that the relationship between FIB and LY% can be used to determine the prognosis of NSCLC.…”
Section: Introductionmentioning
confidence: 99%